The European debt crisis and its implications on the Macedonian Economy - Fiti, Taki; Tashevska, Biljana (Center for Economic Analyses, 2013)
This article provides an overview of the roots of the European debt crisis, which cannot be attributed only to the large fiscal stimulus undertaken by the governments as a response to the global financial crisis of 2007. It results also from the specific design of the Eurozone and the disparities among countries, as well as to fiscal and financial imbalances, especially the previous credit boom and real estate bubble in some peripheral countries. European leaders now face numerous dilemmas concerning the implemented fiscal austerity measures and the appropriate exit strategies (proposals range from enhanced decentralized coordination of fiscal policies, to structural reforms and to a banking and fiscal union). In the end, some of the implications of the European crisis on the financial, real and fiscal sector of the Macedonian economy are examined. Based on the analysis, the article offers lessons about the fiscal policy and public debt of the Republic of Macedonia.
Keywords: European debt crisis, fiscal and financial imbalances, government bond yield, fiscal consolidation, Republic of Macedonia